2004
DOI: 10.1111/j.1464-410x.2004.04979.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term results of sacral neuromodulation for women with urinary retention

Abstract: RESULTSThere were 20 patients (77%) still voiding spontaneously at the time of review (with two having deactivated their stimulator because of pregnancy). Fourteen patients (54%) required revision surgery, and the most common complications included loss of efficacy, implant-related discomfort and leg pain. The mean postvoid residual volume was 75 mL and mean maximum flow rate 20.8 mL/s. CONCLUSIONIn young women with retention, for whom there is still no alternative to lifelong selfcatheterization, sacral neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
1
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(43 citation statements)
references
References 27 publications
(13 reference statements)
2
36
1
4
Order By: Relevance
“…Had we separated the neurogenic UR from idiopathic, non-obstructive UR in our analysis, we may have been able to show more meaningful outcomes. Recent reports on the e¡ect of SNS on idiopathic UR note improved success among patients with notable spasticity and hyperactivity of the pelvic £oor musculature [Swinn et al, 2000;Dasgupta et al, 2004].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Had we separated the neurogenic UR from idiopathic, non-obstructive UR in our analysis, we may have been able to show more meaningful outcomes. Recent reports on the e¡ect of SNS on idiopathic UR note improved success among patients with notable spasticity and hyperactivity of the pelvic £oor musculature [Swinn et al, 2000;Dasgupta et al, 2004].…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism of action is not fully understood, voiding dysfunction at both extremes of U/F and UR seem to respond well, with long-term success and safety noted by numerous studies [Bosch and Groen, 2000;Chartier-Kastler et al, 2000;Hassouna et al, 2000;Siegel et al, 2000;Janknegt et al, 2001;Jonas et al, 2001;Dasgupta et al, 2004;Brazzelli et al, 2006]. Other pathological conditions within the pelvis have also appreciated bene¢t from SNS therapy, to include chronic pelvic pain, constipation/obstipation, irritable bowel syndrome, and fecal incontinence Kene¢ck and Christiansen, 2004;Peters and Konstandt, 2004;Bernstein and Peters, 2005;Jarrett, 2005].…”
Section: Introductionmentioning
confidence: 99%
“…Latini et al 44 reported that 90% of patients maintained a 50% reduction of urge incontinence symptoms (median follow-up, ϳ1 year), and Siegel's group 45 reported that ϳ70% of their patients indicated an improvement of Ͼ50% (mean follow-up, 22 months). In women with retention due to Fowler's syndrome, nearly 80% of patients implanted were reported to have persistent benefit, 46 although 54% had required revision procedures. Some studies, however, have suggested a decline of effectiveness over time.…”
Section: Figmentioning
confidence: 99%
“…54 Different groups have published their long term results in recent years. [55][56][57] They all conclude that SNS therapy is safe and effective (Table I). …”
Section: Clinical Resultsmentioning
confidence: 99%